PERAN HUKUM BISNIS DALAM MENCIPTAKAN KEPASTIAN HUKUM DAN IKLIM USAHA YANG BERKELANJUTAN DI INDONESIA - Elyana Hutahaean; Gunardi Gunardi; Dyah Bayu Framesthi (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
Business law is a set of legal norms and regulations that govern economic activities and legal relationships among business actors. The existence of business law is essential in creating legal certainty, protecting business actors and consumers, and supporting the development of a healthy and sustainable business environment. This study aims to analyze the role of business law in regulating economic activities and its contribution to creating legal certainty and improving the investment climate in Indonesia. The research method employed is normative legal research using statutory and conceptual approaches. The research data were obtained through library research, including legislation, academic books, and relevant scholarly literature related to business law. The results indicate that business law plays a significant role as an instrument for regulating business activities, providing legal protection for business actors and consumers, and offering mechanisms for resolving disputes in economic activities. Furthermore, the implementation of business law principles such as transparency, accountability, and legal certainty can enhance investor confidence and promote national economic growth. However, the rapid development of the digital economy requires regulatory adaptation so that business law can accommodate the dynamics of modern economic activities. Therefore, strengthening regulations and effective law enforcement are crucial in creating a fair, stable, and sustainable business environment in Indonesia.